Scaredy Squirrel goes camping - Watt, Mélanie, 1975- (Scaredy Squirrel, 2021)
Afraid of camping, Scaredy Squirrel decides to watch television instead but quickly realizes he needs to plug his television into an outlet, so he makes a plan to brave the great outdoors.